2014
DOI: 10.1021/jp503027h
|View full text |Cite
|
Sign up to set email alerts
|

Structure and IR Vibrational Spectra of Na8[AlSiO4]6(BH4)2: Comparison of Theory and Experiment

Abstract: The structure and IR vibrational spectra of tetrahydroborate sodalite (Na8[AlSiO4]6(BH4)2) were calculated using density functional theory (DFT) methods. The calculations, performed at the GGA hybrid DFT level yield a close agreement with XRD refinements of the structure and allow interpretation of observed bands of the enclosed BH4(–) and the framework and, in particular, a verification of hydrogen positions (Buhl, J.-C., Gesing, T. M., and Rüscher, C. H. Microporous Mesoporous Mater. 2005, 80, 57−63). In a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…2a and c. framework is often not affected by such an exchange [31,32]. Thus, for a detailed analysis of the Li/Na ratio, the spectral region up to 350 cm Figure 4 shows the theoretical prediction of Raman modes for Na 2 Ti 6 O 13 (Figure 4a) and Li 2 Ti 6 O 13 (Figure 4b tions between theory and experiment are in the range observed for other compounds in a previous study on Na 8 [AlSiO 4 ] 6 (BH 4 ) 2 [27]. Small deviations could arise from the fact that a powder is measured and its surface is not perfectly plain.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…2a and c. framework is often not affected by such an exchange [31,32]. Thus, for a detailed analysis of the Li/Na ratio, the spectral region up to 350 cm Figure 4 shows the theoretical prediction of Raman modes for Na 2 Ti 6 O 13 (Figure 4a) and Li 2 Ti 6 O 13 (Figure 4b tions between theory and experiment are in the range observed for other compounds in a previous study on Na 8 [AlSiO 4 ] 6 (BH 4 ) 2 [27]. Small deviations could arise from the fact that a powder is measured and its surface is not perfectly plain.…”
Section: Resultsmentioning
confidence: 63%
“…Standard basis sets of triple-zeta (Ti) and triple-zeta plus polarization (Na, Li, O) quality were taken from the CRYSTAL website [25]. The generalized gradient approximation (GGA) functional according to Perdew, Burke and Ernzerhof (PBE) [26] was applied as it has provided accurate results for spectroscopic properties in a previous study [27] and has been tested for Raman intensities in CRYSTAL14. For Li 2 Ti 6 O 13 and Na 2 Ti 6 O 13 the crystal lattice parameters for calculation were taken from experiment [13] and kept fixed while the atomic positions were fully relaxed in order to obtain a stationary point for the vibration analysis.…”
Section: Experimental and Theoretical Detailsmentioning
confidence: 99%
“…Since the late 1970s it has been recognized that the vibrational features of sodalites vary with cell parameters, which are strongly influenced by the size of the anion hosted within the sodalite β-cage. , These structure–spectra relationships have since been highlighted many times within the literature , and continue to provide insight into sodalite materials with novel compositions. ,− While sodalite vibrational features are generally compared directly against cell parameters determined using XRD, it is also possible to relate these features to the ionic radius of the anion for sodalites with identical cation composition. The frequencies for the major Raman and FTIR peaks as a function of the anion radius are shown in Figure , where it is observed that the two major Raman and four major infrared peak frequencies display a strong linear relationship with anion radius ( R 2 values all >0.9).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in the present work we compare experimental IR spectra and 11 B NMR chemical shifts with calculated results obtained at DFT level for selected intercalated species. The starting material BH 4 –SOD was synthesized as described in our previous study . In the present study the same theoretical setup was used that has been recently applied to BH 4 –SOD and B­(OH) 4 –SOD .…”
Section: Introductionmentioning
confidence: 99%